The Effect of Occupational Safety and Occupational Health on Employee Job Satisfaction in the Production Department of PT. XYZ - Haifa Arfiani Nazhirah; Khaerul Rizal Abdurahman (Formosa Journal of Multidisciplinary Research, 2026)
To ensure organizational sustainability and the achievement of corporate objectives, special attention must be paid to employee job satisfaction, which plays a crucial role in organizational performance. Previous research indicates that job satisfaction is influenced by occupational safety and occupational health, as both contribute to the creation of a safe and comfortable work environment. However, PT. XYZ continues to experience workplace accidents, high absenteeism due to illness, as well as unexplained tardiness and absence. Therefore, this study examines the partial and simultaneous effects of occupational safety and occupational health on employee job satisfaction. A quantitative approach was employed, involving all contract employees in the production division as respondents. Data were collected through questionnaires, interviews, and observation, and subsequently analyzed using SPSS version 27. The results show that occupational safety and occupational health have a significant positive effect on employee job satisfaction.